A Patient with Sub Acute Viral Hepatitis (HEV) and Nonalcoholic Wernicke’s Encephalopathy: A Case Report (Bangladesh Journal of Neuroscience, 2018)
Wernicke’s encephalopathy (WE) is an acute neurological disorder resulting from thiamine deficiency. It is mainly related to alcohol abuse but it can be associated with other conditions such as gastrointestinal disorders like hyperemesis. A 38-year-old man with acute viral hepatitis presented with severe weakness, yellow discoloration of the body, hyperemesis in addition with disorientation, horizontal and vertical gaze-evoked nystagmus. MRI of brain showed typical findings of WE. Adequate treatment with parenteral thiamine was given. Neurological symptoms (Disorientation, Nystagmus and Ataxia) ameliorated during hospital stay and radiological abnormalities markedly improved in a follow up MRI after 2 months. This case suggests that WE may be associated with hyperemesis in non-alcoholic patients. Early thiamine treatment in symptomatic patients may improve prognosis. This extraordinary presentation of WE with hyperemesis, encouraged us to presentthis case history.Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 52-57